Bitcoin: An axiomatic approach and an impossibility theorem - Leshno, Jacob D. and Strack, Philipp (The American Economic Review: Insights)
Bitcoin's main innovation lies in allowing a decentralized system that relies on anonymous, profit-driven miners who can freely join the system. We formalize these properties in three axioms: anonymity of miners, no incentives for miners to consolidate, and no incentive to assuming multiple fake identities. This novel axiomatic formalization allows us to characterize what other protocols are feasible: every protocol with these properties must have the same reward scheme as Bitcoin. This implies an impossibility result for risk-averse miners. Furthermore, any protocol either gives up on some degree of decentralization or its reward scheme is equivalent to Bitcoin's. - Reproduced
Keywords: Cryptocurrencies, Blockchains